2007
DOI: 10.1118/1.2767985
|View full text |Cite
|
Sign up to set email alerts
|

Waveform simulation based on 3D dose distribution for acoustic wave generated by proton beam irradiation

Abstract: A pulsed proton beam is capable of generating an acoustic wave when it is absorbed by a medium. This phenomenon suggests that the acoustic waveform produced may well include information on the three-dimensional ͑3D͒ dose distribution of the proton beam. We simulated acoustic waveforms by using a transmission model based on the Green function and the 3D dose distribution. There was reasonable agreement between the calculated and measured results. The results obtained confirm that the acoustic waveform includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…15,16,19 The only measurement during a therapeutic irradiation 17 was made at conditions, where the entire tumor volume was irradiated at once, requiring also a dose distribution laterally and longitudinally extended over several centimeters with the so-called passive scattering technique. In this scenario, the corresponding ultrasound waves have a complex structure, from which the underlying dose distribution has to be reconstructed, 36 with only limited accuracy for resolving the spread out Bragg peak (SOBP) distribution. A more advanced irradiation technique makes use of active scanning, where a narrow and quasi-monoenergetic proton pencil beam is scanned across the tumor volume with magnetic deflection, adjusting the Bragg peak position in depth by stepwise changes of the proton energy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,19 The only measurement during a therapeutic irradiation 17 was made at conditions, where the entire tumor volume was irradiated at once, requiring also a dose distribution laterally and longitudinally extended over several centimeters with the so-called passive scattering technique. In this scenario, the corresponding ultrasound waves have a complex structure, from which the underlying dose distribution has to be reconstructed, 36 with only limited accuracy for resolving the spread out Bragg peak (SOBP) distribution. A more advanced irradiation technique makes use of active scanning, where a narrow and quasi-monoenergetic proton pencil beam is scanned across the tumor volume with magnetic deflection, adjusting the Bragg peak position in depth by stepwise changes of the proton energy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous protoacoustic measurements have utilized proton sources at dedicated facilities. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on the difference between their characteristic proton spills, the protoacoustic pressure amplitude generated by single-bunch synchrotron spills (<1 µs) is expected to be higher than those generated by either clinical cyclotrons, which typically deliver proton spills with ∼50 µs rise and fall times, or clinical synchrotrons, which typically deliver with ∼200 µs rise and fall times. 22 Given the short (<1 µs) spill times and high (up to 100 mA instantaneous 11 ) proton current capabilities, previous observations of the protoacoustic signal have employed linear accelerator, 6 synchrotron, 7-17 and tandem-accelerator 18 proton sources.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on the difference between their characteristic proton spills, the protoacoustic pressure amplitude generated by single-bunch synchrotron spills (<1 µs) is expected to be higher than those generated by either clinical cyclotrons, which typically deliver proton spills with ∼50 µs rise and fall times, or clinical synchrotrons, which typically deliver with ∼200 µs rise and fall times. 22 Given the short (<1 µs) spill times and high (up to 100 mA instantaneous 11 ) proton current capabilities, previous observations of the protoacoustic signal have employed linear accelerator, 6 synchrotron, [7][8][9][10][11][12][13][14][15][16][17] and tandem-accelerator 18 proton sources. Protoacoustic signals have also been observed using cyclotron-derived proton beams, 6,19 but these have used custom, modifiable beam lines originally built for research before they were applied to clinical therapy use, and the spill rise times were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using high frequency (up to 10 MHz) ultrasound transducers, we have recently shown one dimensional detection of ionoacoustic signals from a 20 MeV proton Bragg peak 15 . Besides several ionoacoustic simulation studies 16 17 18 , in experiments at an advanced hospital-based cyclotron with 230 MeV protons ionoacoustic signals were observed around 10 kHz with hydrophones 19 . Alsanea et al 20 demonstrated ionoacoustic tomography in simulations, however, no experimental study so far has revealed the spatial characteristics of proton beams.…”
mentioning
confidence: 93%